New Media Audiences Hegemony of Lambe Turah's Instagram Account in Social Media as an Active Audience Maker - Aulia, Hanna; Istiqomah, Yulia (Universitas Nahdlatul Ulama Blitar, 2023)
New Media Audiences: Interaction and Fragmentation (Hegemony of Lambe Turah's Instagram Account in Social Media as an Active Audience Maker). In explaining the context of communication, it can be said that the communication process takes place in the context of progress in the era of globalization which has brought various information through technological devices throughout the world which can then influence society as an audience. Trends that exist in the world today are inseparable from the role of communication as a tool used to convey various messages, ideologies and values ​​of life. It cannot be forgotten that every communication process contains a motive behind it as well as the phenomenon of messages received in the form of trends received from social media, including the rise of